Strategi Kepemimpinan Partisipatif dalam Pengambilan Keputusan Publik di Kota Bau-Bau - Ayucandra, Lis; Gazalin, Junaid; Sufiarni, Sufiarni; Haris, Ahmad Dahlan Al; Nurfiyani, Nurfiyani (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research aims to explore participatory leadership strategies in public decision making in Bau-Bau City. A participatory approach to leadership is considered capable of increasing transparency, accountability and community involvement in the policy-making process, so that it can produce more inclusive and sustainable decisions. This research uses a qualitative method with a case study approach. The research results show that participatory leadership in Bau-Bau City is realized through holding development deliberations, preparing budgets based on community needs, and strengthening collaboration between government, community and local organizations. However, challenges such as the low capacity of the community to express their aspirations and bureaucratic obstacles are still the main obstacles. This research recommends strengthening participatory education and bureaucratic reform to support optimal implementation of participatory leadership.